2018
DOI: 10.21037/cdt.2017.12.02
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a hospital-based educational intervention on dietary salt-related knowledge and behaviour in a cardiac care unit population in Lebanon

Abstract: Background: Cardiovascular disease is the most common cause of morbidity and mortality worldwide.Numerous strategies have been effective in reducing cardiovascular disease risk, from pharmacological approaches to lifestyle modification interventions. One of these strategies includes the reduction in dietary sodium which in turn reduces cardiovascular risk by reducing high blood pressure, perhaps the most important cardiovascular risk factor. Methods:We evaluated an educational dietary salt reduction interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…After 4 weeks follow-up, the percentage of correct answers showed that retention of knowledge of students slightly decreased in comparison to the immediate postintervention, however remained above baseline. A similar pattern was seen in a previous study conducted in Lebanon (22). Similarly, a cohort study conducted at Lurio University, Mozambique, evaluating knowledge retention showed a decrease in knowledge after 6 months compared to post-test (31).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…After 4 weeks follow-up, the percentage of correct answers showed that retention of knowledge of students slightly decreased in comparison to the immediate postintervention, however remained above baseline. A similar pattern was seen in a previous study conducted in Lebanon (22). Similarly, a cohort study conducted at Lurio University, Mozambique, evaluating knowledge retention showed a decrease in knowledge after 6 months compared to post-test (31).…”
Section: Discussionsupporting
confidence: 87%
“…Participants were stratified based on based on their responses to seven of the practice questions to low-risk, moderate-risk and high-risk groups (22). These included "check food labels specifically for salt, " "sodium shown on the label the affects purchasing, " try to buy "low salt foods, " "try to buy 'no added salt' food, " "adding salt during food preparation, " "using stock cubes during cooking, " and "adding salt before tasting."…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A realização da educação para a saúde, seja em sessões individuais ou em grupos, possui os objetivos de melhoria dos conhecimentos, das atitudes e da capacidade de mudança. Esse processo deve ser realizado em instituições promotoras de saúde que apresentem escassez destas atividades e em localidades que apresentem alto nível de vulnerabilidade, como em espaços institucionalizados, a fim de reduzir os agravos e desfechos insatisfatórios encontrados e no contínuo planejamento de promover a saúde (LINGAWI; MAHER; AFIFI, 2017;LYU et al, 2017;PERCIVAL et al, 2016;PHADNIS;KAR, 2017;WALSH et al, 2018 CATANOZI, 2014;LEMBECK;SIMAS;JUNIOR, 2018;SPRONK et al, 2014).…”
Section: Discussionunclassified